Effects of Probiotics and Vitamin D3 Supplementation on Sports Performance Markers in Male Mixed Martial Arts Athletes: A Randomized Trial - Katarzyna Przewłócka; Sylwester Kujach; Piotr Sawicki; Paweł Berezka; Zofia Kinga Bytowska; Marcin Folwarski; Kondrat Kowalski; Jan Jacek Kaczor (SpringerOpen, 2023)
Abstract Background Strategies targeted at the intestine microbiome seem to be beneficial for professional athletes. The gut-muscle axis is associated with the inflammatory state, glucose metabolism, mitochondrial function, and central nervous system health. All these mechanisms may affect maximal oxygen uptake, muscle strength, and training adaptation. Moreover, the positive effect of certain bacterial strains may be enhanced by vitamin D. Thus, this study aimed to assess and compare the level of selected markers of sports performance of mixed martial arts (MMA) athletes supplemented with vitamin D3 or probiotics combined with vitamin D3. Methods A 4-week randomized double-blind placebo-controlled clinical trial was conducted with 23 MMA male athletes assigned to the vitamin D3 group (Vit D; n = 12) or probiotics + vitamin D3 group (PRO + VitD; n = 11). Repeated measures of the creatine kinase level, lactate utilization ratio, and anaerobic performance were conducted. Results After 4 weeks of supplementation, we found lower lactate concentrations 60 min after the acute sprint interval in the PRO + VitD group when compared to the Vit D group (4.73 ± 1.62 and 5.88 ± 1.55 mmol/L; p < 0.05). In addition, the intervention improved the total work (232.00 ± 14.06 and 240.72 ± 13.38 J kg−1; p < 0.05), and mean power following the anaerobic exercise protocol (7.73 ± 0.47 and 8.02 ± 0.45 W kg−1; p < 0.05) only in the PRO + VitD group. Moreover, there was an improvement in the lactate utilization ratio in the PRO + VitD group compared with the Vit D group as shown by the percentage of T60/T3 ratio (73.6 ± 6.9 and 65.1 ± 9.9%, respectively; p < 0.05). We also observed elevated serum 25(OH)D3 concentrations after acute sprint interval exercise in both groups, however, there were no significant differences between the groups. Conclusion Four weeks of combined probiotic and vitamin D3 supplementation enhanced lactate utilization and beneficially affected anaerobic performance in MMA athletes.